2019
DOI: 10.1038/s41385-019-0140-x
|View full text |Cite
|
Sign up to set email alerts
|

The EBI2-oxysterol axis promotes the development of intestinal lymphoid structures and colitis

Abstract: The gene encoding for Epstein-Barr virus-induced G-protein-coupled receptor 2 (EBI2) is a risk gene for inflammatory bowel disease (IBD). Together with its oxysterol ligand 7α,25-dihydroxycholesterol, EBI2 mediates migration and differentiation of immune cells. However, the role of EBI2 in the colonic immune system remains insufficiently studied. We found increased mRNA expression of EBI2 and oxysterol-synthesizing enzymes (CH25H, CYP7B1) in the inflamed colon of patients with ulcerative colitis and mice with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 58 publications
7
73
0
Order By: Relevance
“…We demonstrated that oxysterols sensed through the receptor GPR183 function as guidance cues to position ILC3s within intestinal cryptopatches, which is critical for lymphoid tissue formation in the colon (21) (Figure 4). Similar findings have been subsequently reported by two other labs (95, 120). Chu et al found that GPR183 also regulates ILC3 recruitment to the small intestine (but not to the colon), possibly through promoting α4β7 integrin surface expression on ILC3s (95).…”
Section: Ilc Positioning Within Tissuesupporting
confidence: 92%
“…We demonstrated that oxysterols sensed through the receptor GPR183 function as guidance cues to position ILC3s within intestinal cryptopatches, which is critical for lymphoid tissue formation in the colon (21) (Figure 4). Similar findings have been subsequently reported by two other labs (95, 120). Chu et al found that GPR183 also regulates ILC3 recruitment to the small intestine (but not to the colon), possibly through promoting α4β7 integrin surface expression on ILC3s (95).…”
Section: Ilc Positioning Within Tissuesupporting
confidence: 92%
“…Ch25h −/− mice are highly susceptible to DSS-induced colitis. Elevated CH25H intestinal tissue levels in UC patients and animal models of acute colitis have been reported to closely correlate with the disease activity 24 . Consistent with previous reports, we observed increased expression levels of CH25H in murine DSS colitis tissue (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A recent clinical study showed elevated CH25H expression in IBD patients 24 ; CH25H was involved in intestinal fibrosis 25 ; however, the role of CH25H in IBD has not yet been investigated. To our knowledge, this is the first study showing the ability of 25-HC to alleviate intestinal inflammation in colitic mice.…”
mentioning
confidence: 99%
“…Polymorphisms in LXRs were shown to be associated with IBD in a Danish study and the mRNA expression for both LXRs are decreased in CD and UC patients compared to healthy controls [98,100]. Recently, two independent studies reported that both oxysterols, particularly 4β-HC and 25-OHC as well as their metabolizing enzyme levels, were altered in acute or chronic colitis models in mice and in biopsies of human colitis cohorts [101,102]. However, despite evidence showing the relation between oxysterol/LXR receptors and intestinal inflammation, it is difficult to evaluate the precise role of oxysterols and their nuclear receptors during colitis, which needs further investigation.…”
Section: Oxysterols In Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%
“…Moreover, a significant upregulation of EBI2 gene was found in the ileum of CD patients with NOD2 risk allele [104]. The role of EBI2 during intestinal inflammation was recently studied using different mice model of colitis [102,105,106]. Using an innate model of intestinal inflammation, Emgard et al showed that Ebi2 deficient mice were less susceptible to colitis [105].…”
Section: Oxysterols In Inflammatory Bowel Disease (Ibd)mentioning
confidence: 99%